The tunnel of Dosquebradas - Jaramillo-Correa, Fabio; Lalinde, Mauricio; Naranjo-Henao, José Luis (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2009)
To achieve the vial solution of the highway located between Dosquebradas and Santa Rosa de Cabal, in Risaralda state region of Colombia, was necessary to build a tunnel 134 m length, that is part of an helicoidally way solution, allowing between both structures maintain the permissible road grade of 7,0%. Tunnel was bored across green graphitic schists of Arquia Complex. All the road, included tunnel, is developed in curve with a 99,5 m radius, 5,63 m free height and a 10,0 m road wide, included over-wide and berms. Tunnel direction is approximately N-S and schists are oriented 35° in average toward NE and an slope of 40° toward SE. Analysis methodology used for design and construction consisted in performing tridimensional analysis using finite elements, carry out a pre-dimensional analysis for conventional methods, geological and geotechnical evaluation, an use of a sole shotcrete liner reinforced with metallic and polymeric fiber imbibing support lattice steel bar welded arches.